PEMANFAATAN AIR SUNGAI TERHADAP KEJADIAN PENYAKIT KULIT PADA MASYARAKAT PESISIR SUNGAI SIAK DI KECAMATAN RUMBAI PESISIR PEKANBARU - Serly Marici; Mirna Ilza; Dedi Afandi (Program Pascasarjana Universitas Riau, 2018)
Case of incidence of skin disease there is an increase from year to year in the city of Pekanbaru. Rumbai Coastal is the first rank of the highest case of skin disease. in the year 2016 was recorded a total of 4,174 cases per year. The dominant factor causing the transmission of skin disease is the lack of availability of clean water facilities. The purpose of this research is to analyze the influence of water utilization of Siak River for MCK to the incidence of skin diseases in the community living in Coastal of Siak River in Rumbai Pesisir Subdistrict, Analyzing the influence of long stay in Siak River area to the incidence of skin diseases in the community living in coastal river Siak Kecamatan Rumbai Pesisir, and Analyzed the influence of long time contact of water utilization of Siak River for MCK activity with skin disease incident in society that live in coastal of Siak River of Rumbai Pesisir District. Research location on the coast of Siak River in Rumbai Pesisir Subdistrict of Meranti Pandak, Limbungan, and Tebing Tinggi Okura. The research used a survey method of direct observation of spaciousness with qualitative approach, in-depth interviews to informants who were subjected to research, ie people living in coastal areas of Siak River affected by skin disease, TU Puskesmas Rumbai Pesisir, RT / RW who live on the coastal edge of Siak River.The result of this research shows that there is influence of water utilization of Siak River for MCK to the incidence of skin disease in people living in Coastal of Siak River in Rumbai Pesisir Subdistrict, there is no influence of long stay in Siak River area to the incidence of skin disease in society living in coastal river Siak Kecamatan Rumbai Pesisir, and there is influence of long time contact of water utilization of Siak River for MCK activity with skin disease incident in society that live in coastal of Siak River of Rumbai Pesisir Subdistrict. It is expected that people living in the Siak river basin should be moreconcerned with the importance of maintaining personal hygiene of the individual and the environment and awareness to behave in a clean and healthy way (PHBS).